Constructing the invisible - Computer graphics and the end of Optical Media - Ricardo Cedeño Montaña; Christina Vagt (communication +1, 2018)
This media archaeology of early computer graphics tackles the relation between the imaginary and technical media. We focus on the algorithmic procedures and mathematical principles driving 3D computer graphics during the 1970’s and we frame them in a discussion about the end of optical media and a reflection on the current situation in which images, commanded by techno-codes, delineate and structure the dominant code of communication with which we imagine. Even though algorithmic simulations of optical worlds do not represent the end of optical media as Friedrich Kittler once argued, computer graphics can be seen retrospectively as an escalation in the production of invisibility. We introduce Frieder Nake’s concept of ‘subfaces’ to describe digital images as entities that are composed out of visible and invisible processes. The subface constitutes our methodological tool to analyze computer graphics historically, through three early problems of 3D computer graphics. We complement this media archeology of early computer graphics with discussing the dialogue between Kittler and Vilém Flusser on the imaginary or techo-imagination. Note: Download statistics restarted from zero effective January 1, 2024. Please follow this link to see cumulative download statistics from our previous publishing platform: CPO Download Statistics 2012 - 2023
Keywords: Computer graphics; shading; statistics; techno-imagination; Kittler; Flusser